THE DIFFERENTIATION OF SPIRITUAL AND PSYCHOLOGICAL COUNSELING AS AN EPISTEMOLOGICAL PROBLEM - Remigijus Oželis; Vaineta Juškienė (Perspectiva Teológica)
Epistemology, as a theory of knowledge, examines the problems of the nature, origin, structure, and limits of cognition and understanding. It can provide guidelines for individuals on how to establish a relationship with the external environment, find their place in it, or adapt to it. Within the framework of epistemology, we can look at spiritual counseling, whose priority also involves existential questions, the search for answers to issues such as life, suffering, death, love, transcendence, etc. Spiritual counselors are still searching for clear boundaries for their actions and practices. Although spiritual counseling is not equivalent to psychological counseling, in many cases, they are closely related. Common aspects can be found in both types of counseling. These connections are significant for achieving holistic spiritual assistance but often introduce epistemological confusion and difficulties in trying to differentiate these areas. In spiritual counseling, the aim is to approach the individual through the lens of religious belief. While practitioners in both spiritual and psychological counseling employ similar professional skills, it is important to recognize and distinguish the values guiding specialists in both practices. The article seeks to answer the question: what are the major differences and similarities between spiritual and psychological counselling? To justify the distinction and identity of spiritual and psychological counseling, this article seeks to reveal the essence, meaning, differences, and points of connection between these methods of assistance. Research methods: review, analysis, and synthesis of scientific literature and research.